Molecular and morphological evidence reveals three species within the California sister butterfly, Adelpha bredowii (Lepidoptera: Nymphalidae: Limenitidinae) - Prudic, Kathleen L.; Warren, Andrew D.; Llorente-Bousquets, Jorge (Zootaxa, 2008)
In recent decades the butterfly Adelpha bredowii (Lepidoptera: Nymphalidae), known in the USA as the California Sister, has been considered to be a polytypic array of taxa, composed of two, three or four subspecies. The most recent review of the genus (Willmott 2003a) recognized three: A. b. bredowii, A. b. eulalia (= guatemalensis) and A. b. californica. We used mitochondrial (COII) and nuclear (Tpi) DNA sequence data, coupled with a reevaluation of traditional morphological characters, to determine the phylogenetic relationships between members of the A. bredowii complex, and to elucidate their taxonomic status. Phylogenetic analysis of molecular data corroborated the monophyly of each of the three subspecies (sensu Willmott), with the following topology: (bredowii + (eulalia + californica)). Average levels of COII variation among these taxa were much greater than the average variation within each taxon (3.4% vs. 0.2%, respectively). There were no shared alleles among these taxa, even from localities where two lineages (bredowii and eulalia) were collected in exact sympatry and synchrony. The degree of genetic divergence, reciprocal monophyly, and absence of shared alleles between taxa, coupled with unique morphological and distributional attributes of each, strongly suggest that A. bredowii, A. eulalia and A. californica are all species-level taxa, as they are treated herein (rev. stat.). Adelpha bredowii is endemic to western, central and southern Mexico: the syntype female (herein designated Lectotype) most likely originated near Oaxaca City, Oaxaca. Adelpha eulalia occurs from Guatemala, through much of Mexico, to Arizona, New Mexico and Texas, United States (as permanent residents; further north as vagrants), and occurs in exact sympatry with A. bredowii at least in Oaxaca, Mexico, but potentially in much of western and southwestern Mexico. The syntype female of eulalia (herein designated Lectotype) most likely originated from south-central Mexico. Adelpha californica is allopatric with respect to the other two species, occurring in northern Baja California, much of California, far western Nevada, Oregon and Washington. Our results highlight the continuous need for systematic scrutiny of familiar taxa, and raise the prospect that the genus Adelpha may be comprised of many more hidden species.